Focal FDG Uptake in Lung Parenchyma Without Structural Alterations on CT - Tokmak, H. (World Journal of Nuclear Medicine, 2013)
Transient visualization of a FDG avid abnormality in the lungs without any structural lesion is reported in a case of iatrogenic pulmonary microembolism.
Keywords: FDG; Pulmonary embolism; latrogenic